Modulation and Control Strategy for an Isolated and Bidirectional Two-Stage DC-AC converter with a high ripple on the DC-Link to interface Battery with the Single-Phase Grid - Pantaleon E. (2021)
This work was financed by CONCYTEC-FONDECYT within the call for projects E041-01 [Contract Number 176-2018-BM-FT].